Excise Taxation: Features and Problems of Modern Development (Eurasian Scientific Herald, 2022)
The article considers the economic essence, features of the problem of modern development of excise taxation. The experience of establishing excise taxes in the Republic of Uzbekistan was studied, a comparison was made of excise taxation in the Republic of Uzbekistan and abroad. It is proposed to expand the list of excisable goods and improve the procedure for calculating and paying excise tax in the context of modernizing the tax system.